The Healing Power: A Review on the Various Aspects of the Love-Pain Relationship - Tamam, S.; Ahmad, A.H. (Universiti Sains Islam Malaysia, 2024)
Love is mesmerising yetcomplicated.Brainimaging studies of love foundthat many different areas of the brain are involved in processing this intriguingemotion. Just looking or thinking about a loved one causes the releaseofa variety ofneurotransmittersacross the brain.The universal nature of love is manifested in various forms, including the warm feeling felt towards family, child, spouse, pets orfriends.What is more special about love isthatit may have the ability to heal! Astudy was undertaken to investigate scientifically factors underlying the reputed healing power of love through neuroimaging. Theresults of the study,whichwerepublished recentlyproposed abrain connectivity model ofareas that are involved in reducing pain threshold when a loved-one is nearby, termed "Love Heals". This article discussesthe healing power of love with supporting evidences fromprevious studies.Wefocusonthree aspects, namelythe neurochemistry of romantic love, the psychological aspect of emotionand the neuroimaging aspect.